P140: Investigating volunteer perspectives on leading patient-centred practices in the emergency department. (May 2019) - Witt, L.; Oyedokun, T.; Goodridge, D.; Stempien, J.; Graham, T.
Abstract : Introduction : Patient satisfaction is an essential component of effective delivery of quality care in the emergency department (ED). Frequent reflection on current practices is required to detect areas in need of improvement. The Ontario Hospital Association (OHA) outlined five 'Leading Practices' (LPs) targeted to increase patient satisfaction in this setting. The ED volunteers are a group of individuals who have unique perspectives on ED practices that are unbiased by confounders affecting patients and staff. The goal of this study was to explore the unique perspectives of ED volunteers involving what they believe will improve the delivery of patient-centered care, as well as to examine to what extent Saskatoon EDs are embracing the principles outlined in the OHA LPs.Methods : A two-phase mixed methods approach, with a survey followed by interviews that allowed participants to expand on survey findings was used. The pool of 45 ED volunteers was extended the opportunity to participate resulting in 36 survey responses and 6 interviews. The 13 Likert-grade survey questions were generated to align to each of the LPs and allowed room for qualitative feedback. Interview questions were generated following 15 survey responses to expand on the LPs that were rated below average.Results : Analysis of responses identified inefficient ED processes leading to increased waiting times, inefficient patient location, inadequate signage, a lack of physical space, unclean environments, and a lack of staff and volunteer awareness regarding spiritual care and interpreter services, perceptions of received care by patients due to long wait times and level of cultural safety training of ED staff. Themes reduced from interviews yielded common themes such as patient frustration, disorganization, uncomfortable environment, overcrowding, prolonged wait times, and patient misconception of ED processes at Site 1. Themes common to Site 2 included organization, patient-friendly environment, patient misconception of ED processes, and prolonged wait times. Additionally, the volunteers suggested a plethora of interventions that could improve the current processes in Saskatoon's EDs to make them more patient friendly.Conclusion : Saskatoon EDs comply reasonably well to the OHA Leading practices. Surveying ED volunteers provides important insight into current practices and areas for improvement, and should be considered at other sites to improve adherence to the OHA LPs.